Corporate governance, cash holdings and dividends - Ler, Gin Sheng (2008)
We seek to analyze the relationships between corporate governance with cash holdings and dividend payout of firms in Singapore. Because of the growing importance of corporate governance and Singapore, being a country that has high governance standards, we have decided to research on these relationships in this country. Regression analysis is used for a sample size of 650 observations obtained from 130 firms that are listed in the Singapore Stock Exchange from years 2001 to 2005. In our results, we conclude that there is no clear-cut relationship between cash holdings and corporate governance. However, there is a positive relationship between dividend payout and corporate governance. Further on, we also find that there is positive relationship between cash holdings and dividend payout. In conclusion, our research is generally consistent with those found in previous literatures.